Recent progress in graphene based ceramic composites: a review. Issue 1 (3rd November 2016) - Markandan, Kalaimani; Chin, Jit Kai; Tan, Michelle T.T.
Abstract: Abstract : Research on graphene has been developing at a relentless pace as it holds the promise of delivering composites with exceptional properties. In particular, the excellent mechanical properties of graphene make it a potentially good reinforcement ingredient in ceramic composites while their impressive electrical conductivity has roused interest in the area of multifunctional applications. However, the potential of graphene can only be fully exploited if they are homogenously embedded into ceramic matrices. Thus, suitable processing route is critical in obtaining ceramic composites with desired properties. This paper reviews the current understanding of graphene ceramic matrix composites (GCMC) with three particular topics: (i) principles and techniques for graphene dispersion, (ii) processing of GCMC, and (iii) effects of graphene on properties of GCMC. Besides, toughening mechanisms and percolation phenomenon that may occur in these composites are elaborated with appropriate examples. Challenges and perspectives for future progress in applications are also highlighted.